2012
DOI: 10.5194/bgd-9-485-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Photo-lability of deep ocean dissolved black carbon

Abstract: Dissolved black carbon (DBC), defined here as condensed aromatics isolated from seawater via PPL solid phase extraction and quantified as benzene polycarboxylic acid oxidation products, is a significant component of the oceanic dissolved organic carbon (DOC) pool. These condensed aromatics are widely distributed in the open ocean and appear to be tens of thousands of years old. As such DBC is regarded as highly refractory. In the current study, the photo-lability of DBC, DOC and coloured dissolved organ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
142
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(155 citation statements)
references
References 45 publications
13
142
0
Order By: Relevance
“…This is verified by the higher O/C and H/C ratio as well as by the much lower aromaticity index than typically observed for black carbon compounds Koch and Dittmar, 2006). Stubbins et al (2012) previously demonstrated that highly condensed compounds are photolabile and degrade during exposition to UV-radiation in the surface ocean. This mechanism removes the black carbon from the analytical window, potentially preserving the old carbon as transformed DOM compounds.…”
Section: Chemical Information On the Most Persistent Dom: The Island mentioning
confidence: 70%
“…This is verified by the higher O/C and H/C ratio as well as by the much lower aromaticity index than typically observed for black carbon compounds Koch and Dittmar, 2006). Stubbins et al (2012) previously demonstrated that highly condensed compounds are photolabile and degrade during exposition to UV-radiation in the surface ocean. This mechanism removes the black carbon from the analytical window, potentially preserving the old carbon as transformed DOM compounds.…”
Section: Chemical Information On the Most Persistent Dom: The Island mentioning
confidence: 70%
“…This may indicate degradation processes that remove aromatic BC with transport to the open ocean (e.g. photo-oxidation; Stubbins et al, 2012a). Despite the limited number of BC 14 C studies, it is interesting to note the disparity between Δ 14 C values as isolated by SPE and UDOC.…”
Section: Spe-doc and Bc Cyclingmentioning
confidence: 99%
“…We assume BC at Station M is representative of open ocean BC (with small contributions from riverine anthropogenic sources) (Coppola et al, 2014;Masiello and Druffel, 1998). UV oxidation plays a role in degrading highly aromatic BC in the land-to-ocean transit and may remove these structures upon entering the open ocean (Stubbins et al, 2012a;Masiello and Louchouarn, 2013;Myers-Pigg et al, 2015). Coastal BC may be influenced by anthropogenic riverine BC more directly, as urban water discharge is a primary source of Southern California coastal water pollution (Dwight et al, 2002).…”
Section: Spe-doc and Bc Cyclingmentioning
confidence: 99%
See 2 more Smart Citations